Local Responses and Systemic Induced Resistance Mediated by Ectomycorrhizal Fungi - Dreischhoff, Steven; Das, Ishani S.; Jakobi, Mareike; Kasper, Karl; Polle, Andrea (Frontiers in Plant Science, 2020)
Ectomycorrhizal fungi (EMF) grow as saprotrophs in soil and interact with plants, forming mutualistic associations with roots of many economically and ecologically important forest tree genera. EMF ensheath the root tips and produce an extensive extramatrical mycelium for nutrient uptake from the soil. In contrast to other mycorrhizal fungal symbioses, EMF do not invade plant cells but form an interface for nutrient exchange adjacent to the cortex cells. The interaction of roots and ectomycorrhizal fungi affects host stress resistance but uncovering the underlying molecular mechanisms is an emerging topic. Here, we focused on local and systemic effects of EMF modulating defenses against insects or pathogens in aboveground tissues in comparison with arbuscular mycorrhizal induced systemic resistance. Molecular studies indicate a role of chitin in defense activation by EMF in local tissues and an immune response that is induced by yet unknown signals in aboveground tissues. Volatile organic compounds may be involved in long-distance communication between below- and aboveground tissues, in addition to metabolite signals in the xylem or phloem. In leaves of EMF-colonized plants, jasmonate signaling is involved in transcriptional re-wiring, leading to metabolic shifts in the secondary and nitrogen-based defense metabolism but cross talk with salicylate-related signaling is likely. Ectomycorrhizal-induced plant immunity shares commonalities with systemic acquired resistance and induced systemic resistance. We highlight novel developments and provide a guide to future research directions in EMF-induced resistance.